Fatores que influenciam a cooperação em humanos - Mourão, Rochele Vasconcelos Castelo Branco (2012)
Human cooperation is fundamentally affected by reciprocal exchange, but it is also remarkably common on the context of large and symbolically marked in-groups, which promote cooperation through the feeling of belonging to a group. In this thesis, two empirical articles were produced in order to investigate how human cooperation is affected by factors such as reciprocity, in-group behavior, in-group markers and gender. We investigated this subject through the administration of online games consisting of token donations, on which the subjects faced virtual players controlled by the experiment. We found that cooperative behavior is strongly influenced by reciprocity, and it is also affected by the in-group behavior, observed on the context of the social variables place of birth, ethnicity, and religions, once all of them acted as in-group markers. The subjects´ in-group behavior was enhanced when they played with generous in-group opponents, but weakened when their in-group opponents were non-generous. It was also found that cooperation is not affected by gender, but men and women cooperated in different ways under the influence of reciprocity and in-group behavior. Women are much more reciprocal on their cooperative behavior and men are less willing to cooperate with outgroupers, even when they act generously. The overall results contribute to a better understanding of the adaptive value of cooperation, reciprocity and in-group behavior on the solution of important challenges through the human evolutionary history